Comparison of Feeding Efficiency and Hospital Mortality between Small Bowel and Nasogastric Tube Feeding in Critically Ill Patients at High Nutritional Risk - Wang, Wei-Ning (Nutrients, 2020)
Nasogastric tube enteral nutrition (NGEN) should be initiated within 48 h for patients at high nutritional risk. However, whether small bowel enteral nutrition (SBEN) should be routinely used instead of NGEN to improve hospital mortality remains unclear. We retrospectively analyzed 113 critically ill patients with modified Nutrition Risk in Critically Ill (mNUTRIC) score ≥ 5 and feeding volume < 750 mL/day in the first week of their stay in the intensive care unit (ICU). Age, sex, mNUTRIC score, and Acute Physiology and Chronic Health Evaluation II (APACHE II) score were matched in the SBEN (n = 48) and NGEN (n = 65) groups. Through a univariate analysis, factors associated with hospital mortality were SBEN group (hazard ratio (HR), 0.56; 95% confidence interval (CI), 0.31–1.00), Simplified Organ Failure Assessment (SOFA) score on day 7 (HR, 1.12; 95% CI, 1.03–1.22), and energy intake achievement rate < 65% (HR, 2.53; 95% CI, 1.25–5.11). A multivariate analysis indicated that energy intake achievement rate < 65% on the third follow-up day (HR, 2.29; 95% CI, 1.12–4.69) was the only factor independently associated with mortality. We suggest initiation of SBEN on the seventh ICU day before parenteral nutrition initiation for critically ill patients at high nutrition risk.